Hepatoprotection of Probiotics Against Non-Alcoholic Fatty Liver Disease in vivo: A Systematic Review - Sabirin, Faezah; Lim, Siong Meng; Neoh, Chin Fen; Ramasamy, Kalavathy (Frontiers in Nutrition, 2022)
Probiotic supplements have been increasingly reported for their usefulness in delaying the development and progression of non-alcoholic fatty liver disease (NAFLD). Literature on the impact of probiotics on NAFLD covered various aspects of the disease. This study was undertaken to systematically review in vivo findings on hepatoprotection of probiotics against NAFLD. Literature search was performed through Cochrane, PubMed/ MEDLINE, Embase and Web of Science databases. Intervention(s) of known probiotics in NAFLD-induced animal model with at least one measurable NAFLD-related parameter were included. The data was extracted by all authors independently. Quality assessment was conducted using the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE’s) Risk of Bias (RoB) tool. P-values of measures were compared inter- and intra-study for each parameter. Forty-four probiotic-based studies of NAFLD-induced rodents were shortlisted. The majority of the studies were presented with low/ unclear risk of bias. Probiotics improved the histopathology of NAFLD rodents (primary outcome). Most of the probiotic supplemented NAFLD rodents were presented with mixed effects on serum liver enzymes but improved hepatic and serum lipid profiles (including increased serum high-density lipoprotein cholesterol). The findings were generally accompanied by downregulation of hepatic lipogenic, oxidative and inflammatory signallings. Probiotics were found to modulate gut microbiota composition and its products, as well as intestinal permeability. Probiotics also resulted in better glycaemic control and reduced liver weight. Altogether, the present qualitative appraisals strongly implied the hepatoprotective potential of probiotics against NAFLD in vivo.